PENGAMANAN ASET PRASARANA JALAN DAN BANGUNAN PT X - Sara Rizka Rotua Manurung; Ria Arifianti (POLITEKNIK LP3I JAKARTA, 2025)
Asset security encompasses control and regulation activities in asset management to ensure proper utilization.. The security of road infrastructure and building assets at PT X is crucial for maintaining sustainable public transportation operations in DKI Jakarta Province. This research aims to understand asset security based on theory by (Agus Puji & Riyanto, 2012) using three main indicators: administrative security, physical security, and legal security. The research employs a descriptive qualitative method with data collected through observation, interviews, and document analysis. The results show that PT X has implemented administrative security through comprehensive asset recording and ownership documentation. However, challenges exist in asset utilization that is still under discussion for utilization schemes to ensure benefits for both parties. Physical security has been implemented with advanced technology security systems and regular guarding. Legal security shows that local government regulations and internal regulations are already running side by side. PT X needs to highlight improvements in administrative systems and physical security standards, as well as strengthening legal policies in PT X asset management. With an integrated security strategy, PT X infrastructure assets are expected to continue benefiting the public and supporting Jakarta's development as a global city with modern and sustainable transportation systems.